2017
DOI: 10.1016/s2213-2600(17)30207-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of exacerbations in patients with chronic obstructive pulmonary disease: an analysis of the SPIROMICS cohort

Abstract: Background Current treatment strategies to stratify exacerbation risk rely on history of ≥2 events in the previous year. To understand year-to-year variability and factors associated with consistent exacerbations over time, we present a prospective analysis of the SPIROMICS cohort. Methods We analyzed SPIROMICS participants with COPD and three years of prospective data (n=1,105). We classified participants according to yearly exacerbation frequency. Stepwise logistic regression compared factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
203
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(231 citation statements)
references
References 18 publications
12
203
4
Order By: Relevance
“…National Institute for Health and Care Excellence guidelines state that triple therapy is cost-effective only in patients who have FEV 1 <50% predicted and frequent exacerbations (two or more in past 12 months) 86,90. In this regard, it is interesting that only 2.1% of patients in the SPIROMICS cohort, of whom 30% had severe airflow obstruction, had two or more exacerbations in each year over a 3-year period 91. Therefore, the frequent exacerbator phenotype appears to be much less common than reported in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points (ECLIPSE) study 92.…”
Section: Future Directions: Triple Therapy and Beyondmentioning
confidence: 95%
“…National Institute for Health and Care Excellence guidelines state that triple therapy is cost-effective only in patients who have FEV 1 <50% predicted and frequent exacerbations (two or more in past 12 months) 86,90. In this regard, it is interesting that only 2.1% of patients in the SPIROMICS cohort, of whom 30% had severe airflow obstruction, had two or more exacerbations in each year over a 3-year period 91. Therefore, the frequent exacerbator phenotype appears to be much less common than reported in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points (ECLIPSE) study 92.…”
Section: Future Directions: Triple Therapy and Beyondmentioning
confidence: 95%
“…This favorable difference is unexpected, as compliance is unlikely to be a major issue in a clinical trial where adherence levels are usually high, although this, of course, is a potential advantage for single-inhaler triple therapy in real life. The SPIROMICS data33 show that patients who are used to exacerbation have higher small airways impairment than the other patients, providing a possible explanation for the reason why extrafine BDP/FF/GLY was more effective in this population than large-particle formulations.…”
Section: Introductionmentioning
confidence: 96%
“…A recent analysis from the SPIROMICS study showed an association between small airways disease and the consistent exacerbator phenotype (defined as patient with one exacerbation every year for the 3-year follow-up). The increased computed tomography-defined small airways abnormality was one of the most important variables associated with patients who consistently had acute exacerbations together with previous acute exacerbations and increased CAT score 33. In the TRILOGY study both interventions were delivered by the same inhaler type (pMDI), both formulations were extrafine, and the drugs were inhaled via the same device.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is characterized by chronic inflammation affecting the airway, lung parenchyma and pulmonary vascular system (1). Infiltration of inflammatory cells such as alveolar macrophages, T lymphocytes, particularly CD8 + T cells, and neutrophils leads to the release of inflammatory mediators, including leukotriene B4 (LTB4), interleukin-8 (IL-8) and tumor necrosis factor (TNF)-α (2,3).…”
Section: Introductionmentioning
confidence: 99%